Model Studi Hadis Metode Mutakhir Ide Masyarakat 5.0 - Mahmud; Wahyudin Darmalaksana; Tedi Priatna (Gunung Djati Conference Series, 2022)
This study aims to design a hadith study model to be involved in realizing the idea of society 5.0. This study uses a qualitative approach by applying the analytical descriptive method. The formal object of this research is the study of hadith in a broad sense, while the material object is the latest relevant method to realize the idea of society 5.0 as a research context. The results of this research and discussion propose the findings of the design of the hadith study model, especially through the application of the design thinking method and Higher Order Thinking Skills to transform hadith into the form of society 5.0. This study concludes that the use of the hadith study model design with the latest methods to realize the reality of society 5.0 requires a review of the classical hadith study habits through continuous testing until a more appropriate model is found.